Comparison of the inflammatory and stress response between sprint interval swimming and running - Casuso, R. A.; Aragon-Vela, J.; Huertas, J. R.; Ruiz-Ariza, A.; Martinez-Lopez, E. J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The aim of the study was to compare myocellular damage, metabolic stress, and inflammatory responses as well as circulating sodium (Na+) and potassium (K+) between a single sprint swimming and running training. Eighteen subjects regularly involved in swimming and running training for at least 2 years were recruited. The subjects performed 8 × 30 seconds "all out" exercise on different days either by running or by swimming in a random order. Blood was collected before each training session, after the cessation of exercise (post) and after 2 hours of rest (2 hours). We then analyzed tumor necrosis factor alpha (TNF-a), interleukin 10 (IL-10), interleukin 6 (IL-6), cortisol, creatine kinase MB isoform (CK-MB), lactate dehydrogenase (LDH), K+, and Na+. Neither TNF-a nor IL-10 differed between swimming and running. Most of the subjects showed a non-statistically significant increase of LDH and CK-MB after swimming. On the other hand, IL-6 (P < .05) and cortisol (P < .05) were significantly lower after 2 hours of swimming than after running. In addition, post-exercise K+ was significantly lower (P < .001) for swimming than for running. Our results provide evidence of similar inflammatory responses between exercise modes but lower metabolic stress in response to swimming than in response to running.